Review on Techniques for On-Line Monitoring of Resistance Spot Welding Process. (7th December 2013) - Ma, Yanhua; Wu, Pei; Xuan, Chuanzhong; Zhang, Yongan; Su, He
Abstract : Resistance spot welding has been widely used for joining sheet metals, especially in automotive and aerospace industries. However, since the formation of weld nugget is invisible in resistance spot welding, traditionally off-line destructive test is applied for inspection of the weld quality, which is costly and inefficient. Therefore, in recent years, a lot of efforts have been made in estimating or detecting the weld quality nondestructively by on-line welding parameter monitoring. This paper presents a review on techniques of monitoring resistance spot welding process or weld quality, and the advantages as well as limitations of these techniques are discussed.